Studies on the Dipterocarpaceae of Borneo, II. Ant stipule-brood sites and extra floral nectary association in saplings of Shorea macrophylla [sect. Pachycarpae] in Sarawak, Malaysian Borneo - Wong, Sin Yeng; Boyce., Peter C. (Firenze University Press, 2020)
The presence of stipular and leaf blade extra floral nectaries and associated ant activity, including brood raising within stipules, is reported for saplings of Shorea macrophylla [sect. Pachycarpae] in Kuching Division, Sarawak.